PELATIHAN AKSI BELAJAR CERDAS DI SMK HAFSHAWATY ZAINUL HASAN GENGGONG PROBOLINGGO - AZIZ, ABD (Kalam Nusantara Institute, 2023)
The Smart Action Training held at SMK Hafshawaty Zainul Hasan Genggong Probolinggo on November 27-28, 2023 aims to improve students' skills and competencies in facing the challenges of an increasingly competitive world of work. The program is designed as an effort to combine theoretical knowledge with hands-on practice, so as to produce graduates who are ready to work and have high competitiveness. The training includes various modules covering the development of soft skills such as effective communication, teamwork, and leadership, as well as the enhancement of hard skills relevant to each student's vocational field. The training methodology involves interactive lectures, simulations, group discussions, and practical projects directed by industry experts and practitioners. Evaluation of the training outcomes showed significant improvements in participants' technical and non-technical skills. In addition, feedback from students and instructors indicated that the program was very effective in motivating students to learn more vigorously and be solution-oriented. The conclusion of this training is that the integration of smart action in the vocational education curriculum can make a positive contribution to the development of students' competencies and their readiness to enter the workforce.